Heatconducting through the damplayer - Slavinec, Mitja; Fras, Maja; Zavec Pavlinič, Daniela; B. Mekjavić, Igor (Anali PAZU, 2022)
The article presents the heat transfer through successive layers of different absorbent, which may be damp. Boundary condition on the outside is the constant heat flow density. The model is one-dimensional and is based on the heat diffusion equation for the heat transfer. It gives the time dependence temperature field in the direction perpendicular to the layers. The model takes into account the level of humidity, so it is suitable for the absorbent layer such as textiles. According to the matching simulation results with measured, the simulation used to describe heat transfer through protective clothing. Numerical simulations allow for the extension of any number of different layers, thereby allowing measurements of heat conduction through different clothing or forecast conditions for various structures protective clothing layers and the influence of humidity on the level of protection.